A Forecasting : Bitcoin Price with the ARIMA Method to Help Swing Traders Made Decision - Helynda Mulya Arga Retha; Gilberto Daniel Dwi Putra Taslim (Internasional Journal of Data Science, Engineering, and Anaylitics, 2022)
Abstract: The economic situation is greatly affected by the pandemic. It causes people to look for ways to keep their money safe even if they can make a profit. One of the answers to that question is various investment products such as stocks, bonds, mutual funds, and cryptocurrency. Cryptocurrency or commonly called Cryptocurrency is a digital asset used to exchange. Cryptocurrency today has become a very remarkable phenomenon, especially since entering the era of the COVID 19 pandemic. Bitcoin is a digital currency created in 2009 by Satoshi Nakamoto. Cryptocurrency price movements have patterns and are predictable. The effort to make this prediction is called forecasting. Methods research on this paper using ARIMA methods. The forecasting results for the next five periods of the Bitcoin price show a linear line at the price of USD 48065.1.